Maternal region of birth and stillbirth in Victoria, Australia 2000–2011: A retrospective cohort study of Victorian perinatal data - Davies-Tuck, Miranda L.; Davey, Mary-Ann; Wallace, Euan M. (PLOS ONE, 2017)
Background There is growing evidence from high-income countries that maternal country of birth is a risk factor for stillbirth. We aimed to examine the association between maternal region of birth and stillbirth between 2000 and 2011 inclusive in Victoria, Australia. Methods Retrospective population based cohort study of all singleton births at 24 or more weeks gestational age from 2000–2011 in Victoria, Australia. Stillbirths due to termination of pregnancy, babies with congenital anomalies and Indigenous mothers were excluded. Main Outcome Measure: Stillbirth. Results Over the 12-year period there were 685,869 singleton births and 2299 stillbirths, giving an overall stillbirth rate of 3·4 per 1000 births. After adjustment for risk factors, compared to women born in Australia/New Zealand, women born in South Asia (aOR 1.27, 95% CI 1.01–1.53, p = 0.01), were more likely to have a stillbirth whereas women born in South East and East Asia were (aOR 0.60, (95% CI 0.49–0.72, p<0.001) less likely to have a stillbirth. Additionally, the increasing rate of stillbirth as gestation length progressed began to rise earlier and more steeply in the South Asian compared to Australian/New Zealand born women. The following risk factors were also significantly associated with an increased odds of stillbirth in multivariate analyses: maternal age <20 and 35 years and more, nulliparity, low socio-economic status, previous stillbirth, no ultrasound reported in 1st trimester, pre-existing hypertension, antepartum haemorrhage and failure to detect growth restriction antenatally. Conclusion Maternal region of birth is an independent risk factor for stillbirth. Improvements in the rate of stillbirth, particularly late pregnancy stillbirth, are likely to be gained in high-income settings where clinical care is informed by maternal region of birth.